Sodium‐glucose cotransporter 2 inhibitor luseogliflozin improves glycaemic control, assessed by continuous glucose monitoring, even on a low‐carbohydrate diet. Issue 7 (15th January 2016) - Nishimura, R.; Omiya, H.; Sugio, K.; Ubukata, M.; Sakai, S.; Samukawa, Y.
Abstract : This randomized, double‐blind, placebo‐controlled, crossover study was the first to determine the effects of luseogliflozin in combination with a low‐carbohydrate diet (LCD) on 24‐h glucose variability, assessed by continuous glucose monitoring (CGM). A total of 18 Japanese patients with type 2 diabetes were randomized into two groups, in which patients first received luseogliflozin 2.5 mg once daily then placebo for 8 days each, or vice versa. Patients took luseogliflozin or placebo with a normal‐carbohydrate diet (NCD) on day 7 and with the LCD on day 8. CGM was performed on both days. Luseogliflozin significantly reduced glucose exposure in terms of the area under the curve over the course of 24 h when administered with the NCD (difference vs placebo: −555.6 mg/dl·h [1 mg/dl = 0.0556 mmol/l]; p < 0.001) or with the LCD (−660.7 mg/dl·h; p < 0.001). No hypoglycaemia was observed over 24 h with either diet. Although glucose levels were lower with the LCD than with the NCD in the placebo treatment period, luseogliflozin with the LCD improved glycaemic control throughout the day to nearly the same extent as luseogliflozin with the NCD, without inducing hypoglycaemia.